PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI UD PUTRA NGURIPI KECAMATAN MASARAN KABUPATEN SRAGEN - Widyaningrum, Aprilia Putri; Aji, Ambyah Atas (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
This research aims to determine the influence of motivation and work environment on employee work productivity, both partially and simultaneously. The population in this study were employees of UD Putra Nguripi, Masaran District, Sragen Regency. The number of samples taken was 98 respondents using a questionnaire and multiple regression analysis tools with the SPSS 22 program. The results of the analysis from this research show that motivation and the work environment have a significant positive effect on employee performance partially and simultaneously.